NF-κB signaling pathway mechanism in cow intertoe skin inflammation caused by Fusobacterium necrophorum - Zhang, Hefei; Zheng, Jiasan; Sun, Yue; Yang, Chunxue; Yue, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
Background Fusobacterium necrophorum is the main pathogen inducing bovine foot rot. The infected site is often accompanied by a strong inflammatory response, but the specific inflammatory regulatory mechanism remains unclear. Aim A cow skin explants model was established to elucidate the mechanism of F. necrophorum bacillus causing foot rot in cows, and to provide reference for future clinical practice. Methods Cow intertoe skin explants were cultured in vitro, and F. necrophorum bacteria solution and nuclear factor-κB (NF-κB) inhibitor BAY 1-7082 were added to establish an in vitro infection model. Hematoxylin and eosin staining, terminal - deoxynucleotidyl transferase mediated nick end labeling, and immunohistochemistry were used to detect the pathological changes of the skin explants infected with F. necrophorum, the degree of tissue cell apoptosis, and the expression of the apoptosis-related protein Caspase-3, respectively. RT-qPCR, Western blot, and ELISA were used to detect the activation of the NF-κB pathway and inflammatory cytokines by F. necrophorum. Results The intertoe skin structure of cows infected with F. necrophorum changed with different degrees of inflammation, and the degree of tissue cell apoptosis was significantly increased (P < 0.01). In addition, infection with F. necrophorum significantly increased the phosphorylation level of IκBα protein and up-regulated the expression level of NF-κB p65. The high expression and transcriptional activity of NF-κB p65 significantly increased the expression and concentration of the inflammatory cytokines TNF-α, IL-1β, and IL-8, thus inducing the occurrence of an inflammatory response. However, inhibition of NF-κB p65 activity significantly decreased the expression of inflammatory factors in the intertoe skin of cows infected with F. necrophorum. Conclusion F. necrophorum activates NF‐κB signaling pathway by increasing the expression of TNF‐α, IL‐1β, IL‐8 and other inflammatory factors, leading to foot rot in dairy cows.